Marine cave biota of the Tarkhankut Peninsula (Black Sea, Crimea), with emphasis on sponge taxonomic composition, spatial distribution and ecological particularities. (20th July 2015) - Ereskovsky, Alexander V.; Kovtun, Oleg A.; Pronin, Konstantin K.
Abstract : The main objectives of this study are the establishment of a detailed description of five semi-submerged and shallow-water marine caves from the Tarkhankut Peninsula (Crimea), their biological characteristics with particular attention to species composition, and the distribution of sponge assemblages in these caves. Three semi-submerged and two submerged caves with lengths of 9–131 m and volumes of 61–3060 m 3 have been investigated. All of them are karst-abrasive or karst in origin. In the investigated caves, we inventoried seven sponge species. All were recorded species of Porifera belong to the class Demospongiae and have previously been recorded also in adjacent open sea waters. These species are tolerant to different hydrological conditions, mostly temperature and salinity. Some of them have wide geographic distribution. The species composition of sponges from the shallow water caves of Crimea is quite different from the sponge composition in Mediterranean caves. This could be due to the geographic isolation of the Black Sea and the differences in the hydro-chemical parameters of the milieu (water salinity in Tarkhankut is 18–21‰).